Behavioral Aversion to AITC Requires Both Painless and dTRPA1 in Drosophila - Mandel, Samantha J.; Shoaf, Madison L.; Braco, Jason T.; Silver, Wayne L.; Johnson, Erik C. (Frontiers in Neural Circuits, 2018)
There has been disagreement over the functional roles of the painless gene product in the detection and subsequent behavioral aversion to the active ingredient in wasabi, Allyl isothiocyanate (AITC). Originally, painless was reported to eliminate the behavioral aversion to AITC, although subsequent reports suggested that another trpA homolog, dTRPA1, was responsible for AITC aversion. We re-evaluated the role of the painless gene in the detection of AITC, employing several different behavioral assays. Using the Proboscis extension reflex (PER) assay, we observed that AITC did not reduce PER frequencies in painless or dTRPA1 mutants but did in wild-type genotypes. Quantification of food intake showed a significant decline in food consumption in the presence of AITC in wild-type, but not painless mutants. We adapted an oviposition choice assay, and found wild-type oviposit on substrates lacking AITC, in contrast to painless and dTRPA1 mutants. Lastly, tracking individual flies relative to a point source of AITC, showed a consistent clustering of wild-type animals away from the point source, which was absent in painless mutants. We evaluated expression patterns of both dTRPA1 and painless, which showed expression in distinct central and peripheral populations. We identified the transmitter phenotypes of subsets of painless and dTRPA1 neurons and found similar neuropeptides as those expressed by mammalian trpA expressing neurons. Using a calcium reporter, we observed AITC-evoked responses in both painless and dTRPA1 expressing neurons. Collectively, these results reaffirm the necessity of painless in nociceptive behaviors and suggest experiments to further resolve the molecular basis of aversion.